The Effect of Students’ Worksheet Based on Realistic Mathematics Education (RME) towards Mathematical Problem Solving Ability in Vocational Senior High School Students’ - Abi Suwito; Sinta Priciliya; Ervin Oktavianingtyas (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Realistic Mathematics Education (RME) is one of the approach learning that can used for help student more easy understand and apply draft math on a problem with link things around environment student as well as could increase problem solving abilities students. The aim of this research is to knowing influence from implementation of students’ worksheet based on Realistic Mathematics Education (RME) towards problem solving abilities students. The research design used is study quasi experiment with use method pretest-posttest non equivalent control group design.Population in this study were class XII students of Vocational Senior High School and the sample selected are calss XII TBSM and XII TKRO.Research results show that students whose learning using students’ worksheet get a higher problem solving ability score than students in other classes who do not use students’ worksheets.